2022
DOI: 10.1186/s12886-022-02669-4
|View full text |Cite|
|
Sign up to set email alerts
|

Formation and evolution of idiopathic lamellar macular hole-a pilot study

Abstract: Background The developmental pathways and subsequent evolutional processes of idiopathic lamellar macular hole (LMH) were studied with spectrum domain optical coherence tomography (SD-OCT). Methods Twenty-seven eyes of 26 patients of idiopathic LMH with pre-LMH SD-OCT available were retrospectively reviewed. Relevant OCT parameters and best-corrected visual acuity (BCVA) were collected and analyzed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Similar cases had also been documented by Pang et al [3]. More importantly, these observations were in line with a recent longitudinal study reported by Lee et al [27] which illustrated variable tractional pathways in the development of idiopathic LMHs and showed that some of the cases evolved into degenerative configuration in the later stage. This sequential change of LMH help elucidate the possible pathogenesis of LMH with and without LHEP, that is, LMH initially developed as a result of epiretinal traction with OCT showing tractional morphologies, and when the retinal defect became deeper and wider (i.e., when Muller cells were involved), LHEP occurred, as a reaction of Muller cell to the retinal tissue loss, with corresponding OCT morphological changes (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Similar cases had also been documented by Pang et al [3]. More importantly, these observations were in line with a recent longitudinal study reported by Lee et al [27] which illustrated variable tractional pathways in the development of idiopathic LMHs and showed that some of the cases evolved into degenerative configuration in the later stage. This sequential change of LMH help elucidate the possible pathogenesis of LMH with and without LHEP, that is, LMH initially developed as a result of epiretinal traction with OCT showing tractional morphologies, and when the retinal defect became deeper and wider (i.e., when Muller cells were involved), LHEP occurred, as a reaction of Muller cell to the retinal tissue loss, with corresponding OCT morphological changes (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Differential diagnosis should be made based on a pseudo hole that occurs without the true absence of retinal layers and a lamellar hole that occurs with a defect in the inner/outer fovea. [ 6 ]…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the author group reported errors in the reference citation.…”
mentioning
confidence: 99%